Prevalence of metabolic syndrome and its components among type 2 diabetic mellitus Syrian patients according to NCEP-ATP III and IDF diagnostic criteria - Bakir, M Adel; Hammad, Kholoud; Bagdadi, Khaled (Anthropological Review, 2019)
The metabolic syndrome (MetS) is an important group of components responsible of high incidence of cardio-vascular disease (CVD) and stroke among the type 2 diabetic mellitus (DM) patients. Studies on the prevalence of the MetS and its components among DM patients are limited in developing countries and such studies never been done in Syria before. The objectives of current study were two-folds: (a) to investigate the prevalence of MetS in a group of DM Syrian patients as defined by NCEP-ATP Ш and IDF diagnostic criteria, and (b) to identify the individual MetS associated risk factors components in the studied group. A cross-sectional study carried out at one of the diabetic clinics of the health ministry in Damascus, Syria between 2016–2017. A random sample of 424 patients (209 males, 215 females) DM patients aged 40–79 years were participated in this study. Anthropometric indices, blood pressure (BP), fasting blood sugar (FBS), total cholesterol, high density lipoprotein cholesterol (HDL-C), triglycerides (TG) were determined. The overall prevalence of the MetS was 67% and 69.3% according to the NCEP-ATP Ш and IDF criteria, respectively. The prevalence was higher in females and increased with age. According to NCEP/ATP III criteria and for the overall group, high TG was the most prevalent component of the MetS. However, when an IDF criterion was applied, central obesity was the commonest component in the overall group. According to both diagnostic criteria, hypertension was significantly higher in males while central obesity was dominated in females (p